The Association between Cox-2 and MMP-9 with Clinical Staging in NPC Patients - Farhat Farhat; Elvita Rahmi Daulay; Jessy Chrestella (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: Epstein Barr Virus (EBV) infection is responsible for nasopharyngeal carcinoma (NPC). LMP1 as the product of express gene by EBV latent infection is responsible in inducing Matrix Metalloproteinase–9 (MMP-9) and Cyclooxygenase–2 (COX-2). The two factors are associate with the metastasis of cancer and were thought to be a prognostic factor in nasopharyngeal carcinoma patients.  Objective: The aim of this study was to analyze the overexpression of MMP-9 and COX-2 in NPC patients and the combination of those two with the clinical staging of NPC which lead to an evidence of those two in NPC. This study also needed to reveal the association of MMP-9 expression in response of COX-2 expression.  Methods: This study was a cross sectional design study with statistical analytic approach. Samples was paraffin blocks which taken from the patients diagnosed with NPC with non-probability consecutive sampling method and underwent immunohistochemistry staining. Fisher’s exact test and Chi-square test was conducted to analyze the data, significant if P<0.05. Results: From the total 98 samples, we found the highest overexpression of MMP-9, COX-2, and both of them in nasopharyngeal carcinoma were in WHO Type II (80.8%; 78.8%; 78.6%), T3 (35.9%; 40.0%; 38.6%), N3 (53.8%; 53.8%; 60.0%), M1 (69.2%; 67.5%; 75.7%), and stage IV NPC (69.2%; 67.5%; 75.7%), respectively. There were significant association of primary tumor size, lymph node enlargement, the presence of distant metastasis, and clinical staging in the overexpression of MMP-9, COX-2, and both of them, but not histopathological type. There was association between MMP-9 with COX-2 in nasopharyngeal carcinoma patients. Conclusion: Overexpression of MMP-9, COX-2, and both of them occurs correspondence with increase clinical staging. COX-2 is associate with MMP-9 and those two may be used as prognostic biomarker.